2005
DOI: 10.1111/j.1600-6143.2005.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors that Influence Survival with Post-Transplant Lymphoproliferative Disorder in Renal Transplant Recipients: The Israel Penn International Transplant Tumor Registry Experience

Abstract: Significant mortality is associated with posttransplant lymphoproliferative disorder (PTLD) in kidney transplant recipients (KTX). Univariate/multivariate risk factor survival analysis of US PTLD KTX reported to Israel Penn International Transplant Tumor Registry from November 1968 to January 2000 was performed. PTLD presented 18 (median) (range 1-310) months in 402 KTX. Death rates were greater for those diagnosed within 6 months (64%) versus beyond 6 months (54%, p = 0.04). No differences in death risk for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
71
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 17 publications
10
71
0
5
Order By: Relevance
“…Trofe and associates demonstrated that patients with a B-cell-predominant PTLD had a 33% survival rate versus 49% in those without this form. 5 Our patient demographic results followed trends seen in PTLD patients. Nine of the 10 PTLD-positive patients were White males.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Trofe and associates demonstrated that patients with a B-cell-predominant PTLD had a 33% survival rate versus 49% in those without this form. 5 Our patient demographic results followed trends seen in PTLD patients. Nine of the 10 PTLD-positive patients were White males.…”
Section: Discussionsupporting
confidence: 52%
“…1,11 Age-associated mortality is not related to a specific age; however, the time between transplant and diagnosis of PTLD is associated with mortality. 5 Patients who were diagnosed within 1 year after transplant had a greater risk of dying. 5 In our study, half of the patients who succumbed to their illness were diagnosed with PTLD within 1 year of transplant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations